Effects of writers, erasers and readers within miRNA‐related m6A modification in cancers. Issue 1 (26th September 2022) - Feng, Huiru; Yuan, Xiaofei; Wu, Shuting; Yuan, Yue; Cui, Linchong; Lin, Danfan; Peng, Xiaohong; Liu, Xiong; Wang, Fan
Abstract: Background: As one of the most abundant post‐transcriptional mRNA modifications, N6‐methyladenosine (m6A) has attracted extensive attention from scientists. Emerging evidence indicates that m6A modification plays a significant role in cancer‐related signalling pathways. Existing research demonstrates that m6A modifications were also identified in miRNAs and contribute to cancer‐related signalling pathways. Methods: A literature retrieval has been performed to collect m6A‐miRNA‐related original articles published in recent years. Later, a systematic analysis has been conducted to abstract and classify the relationships between m6A modification and miRNAs, and their contributions to tumorigenesis and cancer development. Results: Accumulating literature provides important insights into multiple relationships between m6A modifications and miRNAs. Mechanically, m6A writer and eraser alter pri‐miRNAs m6A levels, and m6A readers could dually modulate pri‐miRNAs processing and pri‐miRNAs degradation. It is also been demonstrated that miRNAs impair m6A regulators' translation to influence m6A medication function in return. Aberrant expressions of m6A regulators and miRNAs could dysregulate proliferative, apoptosis, cell adhesion‐related, and malignant transformation signalling pathways, and contribute to tumour occurrence and development. Conclusion: This review summarizes the interrelationship between m6A modification and miRNAs; highlights the combined effects of each type of m6A regulator and miRNAs in cancers. These findings enhance our understanding of m6A‐miRNAs' multiple interactions and significant modulatory role in tumorigenesis and progression. Abstract : The interactions between m6A modification and miRNAs mainly consist of the following patterns, m6A modification mediates pri‐miRNAs processing (A), miRNAs target 3′s UTR of m6A regulators (B), miRNAs orchestrate with m6A regulators to exert their intrinsic functions (C). Since interactions between m6A modification and miRNAs contribute to cancer‐related pathways, dysregulations of these interactions cause a series of alterations in diverse cancers.